Efek Hipnoterapi untuk Meningkatkan Kualitas Hidup pada Pasien Penyakit Ginjal Kronik: Suatu Laporan Kasus Berbasis Bukti - Chairani, Aisha Putri; Putranto, Rudi; Shatri, Hamzah; Marbun, Maruhum Bonar Hasiholan; Faisal, Edward; Irvianita, Vinandia; Martina, Diah (UI Scholars Hub, 2025)
Chronic Kidney Disease (CKD) is a condition of kidney damage with a decrease in glomerulus filtration rate of 60 ml/min/1.73 m3 for a duration of more than three months. CKD is closely related to the patient’s quality of life because the patient must carry out various lifestyle restrictions to slow the progression of kidney damage. Lifestyle restrictions often cause problems in the psychosocial field that increase the severity of symptoms and decrease kidney function faster. This evidence-based case review was compiled to determine the effectiveness of hypnotherapy in improving the quality of life of CKD patients. Literature searches were conducted in four databases, namely PubMed, Cochrane, EMBASE, and Scopus. There are three literatures that fit the eligibility criteria. The critical review was conducted using guidelines created by the Centre for Evidence-Based Medicine, University of Oxford. Hypnotherapy consistently shows improved quality of life in the form of decreased symptoms of anxiety, depression, drowsiness, fatigue, and improved social functioning and relationships with family. Hypnotherapy can be considered a complementary therapy in the management of CKD patients with minimal side effects by considering the patient’s accessibility and preferences.